2015
DOI: 10.1080/02640414.2015.1127988
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tennis court surfaces on player perceptions and biomechanical response

Abstract: This study aimed to examine player perceptions and biomechanical responses to tennis surfaces and to evaluate the influence of prior clay court experience. Two groups with different clay experiences (experience group, n = 5 and low-experience group, n = 5) performed a 180°turning movement. Three-dimensional ankle and knee movements (50 Hz), plantar pressure of the turning step (100 Hz) and perception data (visual analogue scale questionnaire) were collected for two tennis courts (acrylic and clay). Greater ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…Participants perceived that they were able to complete the slalom course faster and had increased in-shoe grip in TI. It is only through detecting this change that players can actively respond and alter their technique to improve their performance (Morio et al, 2017;Starbuck et al, 2016). Although there was no difference in subjective footwear comfort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants perceived that they were able to complete the slalom course faster and had increased in-shoe grip in TI. It is only through detecting this change that players can actively respond and alter their technique to improve their performance (Morio et al, 2017;Starbuck et al, 2016). Although there was no difference in subjective footwear comfort.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate subjective perception of running speed and in-shoe grip, 150 mm visual analogue scales (VAS) were marked after each maximal trial. The VAS was anchored with the terms 'very slow' to 'very fast' and 'very low to very high' for running speed and in-shoe grip respectively (adapted from Starbuck et al, 2016). Subjective perception of footwear comfort was also assessed using a 150mm VAS after a further two trials at a self-selected submaximal pace, in each insole, after completing the maximum trials.…”
Section: Performance and Subjective Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also hope to incorporate player perceptions into future research. Building on past similar work, 26 the authors would like to determine if professional tennis players notice a difference in a shoe’s sliding ability as the critical area ratio changes through the critical zone uncovered in this work. As players use shoes of various area ratios, the authors will also analyze whether the area ratio affects a shoe’s durability.…”
Section: Discussionmentioning
confidence: 99%
“…A normal load of 33 N was selected for step tests, and 25 N for the slide tests. These loads produced nominal contact pressures across the tread elements for the step (604 kPa) and slide tests (456 kPa), equal to those determined by mechanical shoe contact area tests, which used loads from biomechanical tests on hard court steps and slides [12,18,22,23]. For example, a biomechanics study investigating hard court sliding reported normal loads between 300 and 835 N [12].…”
Section: Experiments Summarymentioning
confidence: 99%